INOVASI ADMINISTRASI PENDIDIKAN DAN PENGARUHNYA TERHADAP EFEKTIVITAS PEMBELAJARAN ABAD 21 - Ika Kumalaisyawati (Jurnal Administrasi Pendidikan Indonesia, 2025)
This study aims to analyze the influence of educational administration innovation on the effectiveness of 21st-century learning in schools. The research approach uses a quantitative method with a survey design. Respondents consisted of 25 teachers from various levels of education in Banyuwangi. The research instrument was a Likert scale questionnaire that measured two variables, namely educational administration innovation (X) and the effectiveness of 21st-century learning (Y). Data analysis was carried out through normality, linearity and simple linear regression tests. The results of the normality test showed that variables X and Y were normally distributed, with p-values ​​of 0.124 and 0.098, respectively. Variables X and Y were also linear with a significance value of 0.003, a coefficient of determination of 0.53, indicating that educational administration innovation contributed 53% to the effectiveness of 21st-century learning. The higher the level of administrative innovation implemented by schools, the better the teachers' ability to implement 21st-century learning. This study emphasizes the importance of administrative digitalization and strengthening data-based management in supporting learning transformation.